The Beauty of Anatomy: Visual Displays and Surgical Education in Early-Nineteenth-Century London - BERKOWITZ, CARIN (Bulletin of the history of medicine, 2011)
The early-nineteenth-century artist, anatomist, and teacher Sir Charles Bell saw anatomy and art as closely related subjects. He taught anatomy to artists and surgeons, illustrated his own anatomical texts, and wrote a treatise on the use of anatomy in art. The author explores the connections among visual displays representing human anatomy, aesthetics, and pedagogical practices for Bell and a particular group of British surgeon-anatomists. Creating anatomical models and drawings was thought to discipline the surgeon's hand, while the study of anatomy and comparative anatomy would discipline the artist's eye. And for Bell, beauty made drawings into better pedagogical tools.